Wood-derived three-dimensional porous carbon-based catalyst, preparation method and application

By introducing Fe, N and S elements into the fibrous biomass raw materials, a three-dimensional porous carbon-based catalyst with high specific surface area was prepared, which solved the problems of high cost and poor stability of traditional catalysts, and achieved efficient oxygen reduction performance and reduced production costs. .

CN119133482APending Publication Date: 2024-12-13XI'AN POLYTECHNIC UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411213813.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-31
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The cathode catalyst of traditional metal air batteries is costly and has poor stability, which cannot meet the needs of large-scale applications, and the preparation of traditional three-dimensional porous carbon materials is complex and costly.

Method used

Using fibrous biomass raw materials that have been treated with delignin, activation and pyrolysis, loading Fe, N and S elements, a three-dimensional porous carbon-based catalyst with high specific surface area is prepared, and through specific impregnation, carbonization and pyrolysis steps, the A catalyst with excellent electrocatalytic activity.

Benefits of technology

The prepared three-dimensional porous carbon-based catalyst has extremely high specific surface area and excellent oxygen reduction properties, which can provide high power density and specific capacity, reduce production costs, and improve the stability of the electrocatalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133482A_ABST
    Figure CN119133482A_ABST
Patent Text Reader

Abstract

The invention discloses a wood-derived three-dimensional porous carbon-based catalyst as well as a preparation method and application thereof. A fiber biomass raw material subjected to delignification, activation and pyrolysis is loaded with a catalyst of an element Fe, an element N and an element S; according to the wood-derived three-dimensional porous carbon-based catalyst, the preparation method and the application provided by the invention, Fe, N and S elements are introduced into a carbon skeleton, and the three-dimensional porous carbon-based catalyst which is high in specific surface area and is loaded with three active elements is finally obtained. The prepared three-dimensional porous carbon-based catalyst has a three-dimensional porous structure, and the material is endowed with an extremely high specific surface area, which means that the material can fully expose active sites, benefits from unique large specific surface area and highly exposed active sites, and shows excellent oxygen reduction performance. When the three-dimensional porous carbon-based catalyst is used as the cathode of the zinc-air battery, excellent power density and specific capacity can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal-air batteries, and in particular to a wood-derived three-dimensional porous carbon-based catalyst, a preparation method and an application thereof. Background Art

[0002] The energy crisis and environmental problems caused by the accelerated consumption of traditional fossil energy have prompted people to develop the next generation of sustainable energy conversion devices. As representatives of emerging energy, fuel cells and metal-air batteries have been widely explored. Among them, zinc-air batteries have become a very promising energy storage technology due to their high energy density, low cost and green environmental protection. However, since the redox reaction kinetics of the zinc-air battery cathode (ORR) is very slow, highly active electrocatalysts are required to accelerate the reaction process.

[0003] Although noble metal and metal oxide catalysts (Pt, RuO2, IrO2, etc.) show excellent electrocatalytic activity, they are unable to meet the needs of large-scale applications due to their high cost, low stability and scarcity. At present, the method of co-doping transition metal elements with non-metallic elements has been reported to show excellent stability and electrocatalytic activity. However, transition metal elements are prone to problems such as agglomeration and migration, which in turn causes the attenuation of the electrocatalytic activity of the catalyst. In addition, traditional three-dimensional porous carbon materials have problems such as complex preparation process and high cost. Therefore, the development of sustainable and efficient electrocatalysts remains an urgent task.

[0004] Biomass materials have the potential advantages of high carbon content, wide sources, renewability and low cost, and have become the preferred precursor for the production of carbon materials. As one of the largest biomass resources in the world, the unique pore structure of wood shows great potential in energy conversion and storage materials. It has been reported that the porous structure uses a multi-channel structure to achieve effective mass transfer and provides abundant active sites, thereby showing extremely high electrocatalytic activity and stability. Therefore, as mentioned above, utilizing and changing the inherent biological structural characteristics of biomass carbon materials is expected to develop cheap and high-performance electrocatalytic materials and promote the development prospects of clean energy and energy storage applications. Summary of the invention

[0005] The main purpose of the present invention is to provide a wood-derived three-dimensional porous carbon-based catalyst, a preparation method and an application, aiming to solve the problem that the cathode catalyst of metal-air batteries is expensive and cannot meet the needs of large-scale applications.

[0006] In order to achieve the above object, the present invention provides a wood-derived three-dimensional porous carbon-based catalyst, comprising:

[0007] The cellulosic biomass raw material after delignification, activation and pyrolysis is loaded with catalysts containing Fe, N and S elements.

[0008] The present invention also provides a preparation method, which is applied to the above-mentioned wood-derived three-dimensional porous carbon-based catalyst, comprising:

[0009] S1. Immersing the fiber biomass raw material in a caustic solution to perform delignification and alkali activation pretreatment to obtain a biomass pre-treated product, wherein the fiber biomass raw material is processed along the growth length direction, and the caustic solution includes one of a sodium hydroxide solution and a potassium hydroxide solution;

[0010] S2, washing and drying the biomass pretreatment product with deionized water, and then heating and carbonizing it in an inert atmosphere to obtain an alkali-activated three-dimensional porous carbon precursor;

[0011] S3, preparing a loaded salt solution by using a sulfur and nitrogen source and a transition metal source;

[0012] S4, adding the three-dimensional porous carbon precursor into the loaded salt solution to complete impregnation and adsorption, thereby obtaining a three-dimensional porous carbon impregnation sample;

[0013] S5. Dry the three-dimensional porous carbon impregnation sample, and then pyrolyze it in an inert atmosphere to finally obtain a three-dimensional porous carbon-based catalyst.

[0014] Furthermore, in step S1, the fiber biomass raw material is balsa wood chips.

[0015] Furthermore, in the step S1, an ultrasonic treatment condition is added to the immersion environment of the caustic solution; and in the step S4, an ultrasonic treatment condition is added to the loaded salt solution environment.

[0016] Furthermore, in the step S1, the concentration of the caustic solution is 2.0 to 3.0 mol / L, and the immersion time is 8 to 15 hours.

[0017] Furthermore, in step S3, the sulfur and nitrogen source is thiourea, the transition metal source is ferric nitrate, the concentration of thiourea in the loaded salt solution is 0.1 to 0.4 mmol per liter, and the concentration of ferric nitrate is 20 to 80 mmol per liter.

[0018] Furthermore, in steps S2 and S5, the drying temperature is 50 to 70 degrees Celsius, and the drying time is 4 to 8 hours.

[0019] Furthermore, in the step S2, the temperature of the heating carbonization is 680 to 720 degrees Celsius, the heating rate is 4 to 6 degrees Celsius per minute, and the heat preservation time is 1.5 to 2.5 hours.

[0020] Furthermore, in the step S5, the pyrolysis temperature is 880 to 920 degrees Celsius, the heating rate is 4 to 6 degrees Celsius per minute, and the heat preservation time is 1.5 to 2.5 hours.

[0021] The present invention also provides an application of a wood-derived three-dimensional porous carbon-based catalyst, wherein the wood-derived three-dimensional porous carbon-based catalyst is used as an oxygen reduction electrocatalyst of a zinc-air battery.

[0022] The wood-derived three-dimensional porous carbon-based catalyst, preparation method and application provided by the present invention introduce Fe, N and S elements into the carbon skeleton, and finally obtain a three-dimensional porous carbon-based catalyst with high specific surface area and loaded with three active elements. The prepared three-dimensional porous carbon-based catalyst has a three-dimensional porous structure, which gives the material an extremely high specific surface area, meaning that the material can fully expose active sites. Benefiting from the unique large specific surface area and highly exposed active sites, the material exhibits excellent oxygen reduction performance. When the three-dimensional porous carbon-based catalyst is used as the cathode of a zinc-air battery, it can provide excellent power density and specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope element mapping diagram of the three-dimensional porous carbon-based catalyst of the first embodiment of the present invention;

[0024] Figure 2 It is an X-ray photoelectron spectroscopy analysis of the three-dimensional porous carbon-based catalyst of the first embodiment of the present invention;

[0025] Figure 3 This is the LSV curve test of the three-dimensional porous carbon-based catalyst at different rotation speeds in the first embodiment of the present invention;

[0026] Figure 4 This is the full cell polarization power density curve of the full cell made of the three-dimensional porous carbon-based catalyst of the first embodiment of the present invention and the commercial Pt / C catalyst;

[0027] Figure 5 The results of the multi-current density continuous discharge test of the full battery made of the three-dimensional porous carbon-based catalyst in the first embodiment of the present invention;

[0028] Figure 6 This is the static discharge-charge cycle curve of the full battery made of the three-dimensional porous carbon-based catalyst in the first embodiment of the present invention;

[0029] Figure 7 is a schematic diagram of a preparation method of a second embodiment of the present invention;

[0030] Figure 8 This is a scanning electron microscope image of the three-dimensional porous carbon-based catalyst of the first embodiment of the present invention;

[0031] Fig. 9This is the test result of the capacitance-voltage characteristic curve of the three-dimensional porous carbon-based catalyst in the electrolyte of the first embodiment of the present invention;

[0032] Fig.10 The results of the specific capacity test of the full cell made of the three-dimensional porous carbon-based catalyst of the first embodiment of the present invention and the full cell of the commercial Pt / C catalyst;

[0033] Fig.11 It is the N2 adsorption-desorption curve test of the first embodiment of the present invention and comparative examples 1 to 3;

[0034] Fig.12 This is the LSV curve test of the first embodiment of the present invention, comparative examples 1 to 3 and commercial Pt / C catalyst.

[0035] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0036] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0037] Those skilled in the art will appreciate that, unless expressly stated otherwise, the singular forms "a", "an", "said", "above", and "the" used herein may also include plural forms. It should be further understood that the term "comprising" used in the specification of the present invention refers to the presence of the features, integers, steps, operations, elements, units, modules, and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, units, modules, components, and / or groups thereof. It should be understood that when we refer to an element as being "connected" or "coupled" to another element, it may be directly connected or coupled to the other element, or there may be intermediate elements. In addition, the "connection" or "coupling" used herein may include wireless connection or wireless coupling. The term "and / or" used herein includes all or any unit and all combinations of one or more associated listed items.

[0038] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.

[0039] Reference Figures 1 to 6 In one embodiment of the present invention, a wood-derived three-dimensional porous carbon-based catalyst comprises:

[0040] The cellulosic biomass raw material after delignification, activation and pyrolysis is loaded with catalysts containing Fe, N and S elements.

[0041] In the present invention, in a preparation process, a balsa wood block (5 mm*15 mm*5 mm) is cut into thin slices with a thickness of less than 1.5 mm along the growth direction to prepare a homemade fiber biomass raw material. A KOH solution is prepared with a concentration of 2.5 mol / L and an immersion time of 10 to 12 hours to obtain a biomass pre-treated product.

[0042] The biomass pretreatment material is rinsed and dried with deionized water to wash away the lignin and the excess caustic soda on the surface. The three-dimensional porous carbon precursor is obtained by heating carbonization in an inert atmosphere, and the alkali activation process is completed in this process. Sulfur and nitrogen sources and transition metal nitrate solutions are prepared and a uniform solution is obtained after stirring. The three-dimensional porous carbon precursor is added to a solution of a loaded salt solution to complete impregnation and adsorption, and a three-dimensional porous carbon impregnation sample is obtained. The three-dimensional porous carbon impregnation sample is dried and then pyrolyzed in an inert atmosphere to finally obtain a three-dimensional porous carbon-based catalyst (i.e., Fe@NSC catalyst). Reference Figure 1 , the three-dimensional porous carbon-based catalyst was analyzed by scanning electron microscopy and the element mapping diagram was obtained. It can be judged that the above process can obtain the dispersion of Fe, N and S elements in a stable manner.

[0043] X-ray photoelectron spectroscopy analysis of Fe@NSC catalyst was completed. Figure 2 The surface element composition and chemical state of Fe@NSC samples were analyzed by X-ray photoelectron spectroscopy. Figure 2 As shown, the doped elements were detected in the Fe@NS sample, including Fe, N, S and other elements.

[0044] In sub-figure (a), the high-resolution C1s spectrum of the Fe@NS sample is mainly composed of four characteristic parts. The characteristic peak at 284.8 electron volts comes from the CC coordination of the carbon substrate; the characteristic peaks at 286.3 electron volts and 293.5 electron volts come from the CS and CN bonds, respectively, proving the effective doping of N and S elements into the carbon skeleton; the characteristic peak at 296.5 electron volts is attributed to the OC=O coordination.

[0045] In the sub-figure (b), the high-resolution Fe2p spectrum of the Fe@NS sample shows that the Fe@NSC material has Fe2p 3 / 2 (711.59 eV and 726.69 eV) and Fe2p 1 / 2 (724.07 eV) characteristic peak, and a satellite peak (717.86 eV). In addition, Fe2p spectrum did not find substances such as Fe3C, so it is believed that Fe is Fe-Nx exists in the form of.

[0046] In the sub-figure (c), the high-resolution N1s spectrum of the Fe@NS sample is mainly composed of five parts, namely pyridinic nitrogen (399.14 electron volts), pyrrolic nitrogen (400 electron volts), graphitic nitrogen (401.28 electron volts), oxidized nitrogen (402.27 electron volts) and Fe-Nx (400.67 electron volts). Generally speaking, increasing the content of pyridinic nitrogen and graphitic nitrogen is beneficial to improving the ORR activity of the material. Among them, pyridinic nitrogen is beneficial to enhancing the adsorption of O2 and promoting the breaking of O=O bonds, while graphitic nitrogen accelerates the electron transfer in the ORR reaction process by improving the conductivity of the material.

[0047] In the high-resolution S2p spectrum of the Fe@NS sample, sulfur is expressed as thiophene sulfur (2p 3 / 2 , 2p 1 / 2 ) and sulfur oxide species (169.4 eV).

[0048] Reference Figure 3 , LSV curves of Fe@NSC catalyst at different rotation speeds in 0.1 mol / L KOH solution saturated with oxygen (the curves and labels are from bottom to top with decreasing rotation speed). The limiting current density of Fe@NSC catalyst increases with increasing rotation speed, and the current density increase interval is stable. The limiting current density of Fe@NSC sample is closer to that of commercial Pt / C catalyst.

[0049] Subsequently, the Fe@NSC catalyst was used as the cathode and a zinc-air battery was assembled. The battery used a zinc plate as the anode, 6.0 mol / L KOH and 0.2 mol / L Zn(CH3COO)2 as the electrolyte. Figure 4 As shown, the open circuit voltage of a single zinc-air battery reaches about 1.42 volts, which is comparable to the open circuit voltage of a full battery with Pt / C as the cathode. The maximum power density of the zinc-air battery assembled based on the Fe@NSC sample reaches 138 milliwatts per square centimeter at a current density of 190 milliamperes per square centimeter, which is much higher than the 125.7 milliwatts per square centimeter (128 milliamperes per square centimeter) based on Pt / C.

[0050] like Figure 5 As shown in the figure, the zinc-air battery assembled with Fe@NSC catalyst was subjected to multi-current density continuous discharge test. At different discharge current densities, it showed a large discharge voltage. In addition, with the increase of current density, its voltage decreased very little, which means that the zinc-air battery assembled with this material has excellent discharge capacity.

[0051] like Figure 6As shown in the figure, the static discharge-charge cycle curve further reveals the cycle stability of the zinc-air battery assembled with the Fe@NSC catalyst. At a high current density (10 mA per square centimeter), the battery was tested with a 5-minute fast charge and a 5-minute fast discharge. The battery ran for 2000 cycles (over 300 hours) and the voltage range drop was negligible.

[0052] In summary, Fe, N and S elements are introduced into the carbon skeleton, and finally a three-dimensional porous carbon-based catalyst with high specific surface area and loaded with three active elements is obtained. The prepared three-dimensional porous carbon-based catalyst has a three-dimensional porous structure, which gives the material an extremely high specific surface area, which means that the material can fully expose the active sites. Benefiting from the unique large specific surface area and highly exposed active sites, the material exhibits excellent oxygen reduction performance. When the three-dimensional porous carbon-based catalyst is used as the cathode of the zinc-air battery, it can provide excellent power density and specific capacity.

[0053] Reference Figure 7 The present invention also provides a preparation method, which is applied to the above-mentioned wood-derived three-dimensional porous carbon-based catalyst, comprising:

[0054] S1. Immersing the fiber biomass raw material in a caustic solution to perform delignification and alkali activation pretreatment to obtain a biomass pre-treated product, wherein the fiber biomass raw material is processed along the growth length direction, and the caustic solution includes one of a sodium hydroxide solution and a potassium hydroxide solution;

[0055] S2, washing and drying the biomass pretreatment product with deionized water, and then heating and carbonizing it in an inert atmosphere to obtain an alkali-activated three-dimensional porous carbon precursor;

[0056] S3, preparing a loaded salt solution by using a sulfur and nitrogen source and a transition metal source;

[0057] S4, adding the three-dimensional porous carbon precursor into the loaded salt solution to complete impregnation and adsorption, thereby obtaining a three-dimensional porous carbon impregnation sample;

[0058] S5. Dry the three-dimensional porous carbon impregnation sample, and then pyrolyze it in an inert atmosphere to finally obtain a three-dimensional porous carbon-based catalyst.

[0059] In the prior art, in step S1, balsa wood blocks (5 mm * 15 mm * 5 mm) are cut into thin slices with a thickness of less than 1.5 mm along the growth direction to make a homemade fiber biomass raw material. A caustic solution (one of a sodium hydroxide solution and a potassium hydroxide solution) of a certain concentration is prepared to immerse the fiber biomass raw material in the solution to remove a large amount of lignin. In a specific implementation process, the caustic solution is a KOH solution with a concentration of 2.5 mol / L, and the immersion time is 10 to 12 hours. When the concentration of the KOH solution decreases, the immersion time will be extended; when the KOH concentration increases, the cost will increase, and the KOH content adsorbed by the fiber biomass raw material will increase, which can easily lead to excessive pore formation in the subsequent activation stage. Through the combination of concentration and time, the two processes of delignification and alkali activation (alkali activation pretreatment) can be combined, which improves the process efficiency while reducing the cost of the entire process. The solubility of the caustic soda solution and its immersion time are particularly important. If the effect is weak, the alkali activation pretreatment process cannot be achieved, and if the effect is too strong, it will lead to the collapse of the three-dimensional porous structure (the specific surface area is greatly reduced).

[0060] In step S2, the biomass pretreatment material is rinsed and dried with deionized water to wash away the lignin and the excess caustic soda on the surface. The characteristics of the rinse also effectively leave the caustic soda inside the biomass pretreatment material. The three-dimensional porous carbon precursor is obtained by heating carbonization in an inert atmosphere, and the alkali activation process is completed in this process. In a specific implementation process, the activation temperature is optimally controlled at 600 to 800 degrees Celsius, the heating rate is selected at 2 to 7 degrees Celsius per minute, and the insulation time is 2 hours; when the heating rate is too fast, the biomass carbonization speed is too fast, resulting in an unstable carbon skeleton; when the heating rate is too low, the activation time is too long, which can easily cause excessive pore formation, and also increases the preparation time and cost.

[0061] In the prior art, in the utilization of fiber biomass raw materials, delignification and alkali activation are two important steps, each of which has a unique role and function, so it is particularly important to treat them separately. Delignification can effectively break the complex structure of cellulose, release cellulose and hemicellulose, and facilitate the subsequent process; however, the chemical methods used in the delignification process, such as acid-base method, organic solvent method, etc., often cause changes in the structure and properties of lignin. Therefore, after delignification, alkali activation treatment of lignin can further improve its structure and properties, and improve its biological activity and application value; generally, alkali activation treatment is arranged after delignification and carbonization, and then soaked in alkaline solution again, and then dried again; alkali activation treatment mainly chemically modifies lignin under alkaline conditions to expose more active groups, such as phenolic hydroxyl groups.

[0062] In step S1 of the present invention, the concentration and time of the caustic solution are combined to combine the delignification and alkali activation (alkali activation pretreatment) processes, thereby improving the process efficiency and reducing the cost of the entire process. In step S2 of the present invention, the biomass pretreatment material is only rinsed without adjusting the pH, so that the caustic in the pore structure of the biomass pretreatment material can be retained, combining carbonization and activation treatment, and reducing the complexity and cost of the entire process.

[0063] In step S3, a sulfur and nitrogen source and a transition metal nitrate solution are prepared and stirred to obtain a uniform solution. In the specific implementation process of the sulfur and nitrogen source and the transition metal source, the specific introduction method of the sulfur and nitrogen source and the introduction method of the transition metal source can be selected according to the actual situation, and the concentration selection is confirmed according to the experimental results. In a specific implementation process, in 100 ml of deionized water, the addition amount of the transition metal nitrate is 0.188 mmol, and the addition amount of thiourea is 5.3 mmol.

[0064] In step S4, the three-dimensional porous carbon precursor is added to the solution of the loaded salt solution to complete impregnation and adsorption, and a three-dimensional porous carbon impregnation sample is obtained. The specific impregnation time is adjusted according to the experimental results, generally more than 5 hours, preferably about 10 hours.

[0065] In step S5, the three-dimensional porous carbon impregnation sample is dried and then pyrolyzed in an inert atmosphere to finally obtain a three-dimensional porous carbon-based catalyst. In a specific implementation process, the final pyrolysis temperature is 850 to 950 degrees Celsius, the heating rate is 2 to 7 degrees Celsius per minute, and the insulation time is 2 hours. It is worth noting that the three-dimensional porous carbon material can be used as a carrier of active elements or as a conductive network in the ORR electrocatalytic process, and the defects on its surface can also be used as active sites for the reaction; when the pyrolysis temperature is too low, the degree of graphitization of the three-dimensional porous carbon material is low, which is not conducive to the ORR reaction process; but when the pyrolysis temperature is too high, the non-metallic elements further volatilize, resulting in excessive development of the pore structure, which in turn causes the collapse of the carbon skeleton. Therefore, the range of the final pyrolysis temperature needs to be selected and formulated based on various characterization results.

[0066] In one embodiment, in step S1, the fiber biomass raw material is balsa wood chips.

[0067] In this embodiment, the fiber shape of the balsa sawdust forms a mesh structure that is beneficial to both the loading process and the use process. The large amount of hydroxyl groups in the cellulose and hemicellulose in the balsa sawdust are more sensitive to an alkaline environment, and both are partially removed in an alkaline medium.

[0068] In one embodiment, in the step S1, ultrasonic treatment conditions are added to the immersion environment of the caustic solution; and in the step S4, ultrasonic treatment conditions are added to the loaded salt solution environment.

[0069] In this embodiment, in step S1, due to the microporous characteristics of the fibrous biomass raw material, adding ultrasonic treatment conditions in the impregnation environment makes the delignification and alkali activation pretreatment processes more thorough, and the intensity of the specific ultrasonic treatment conditions is crucial to the treatment effect in this step, but the optimal parameter point can be found through relevant experimental design. In step S2, due to the microporous characteristics of the three-dimensional porous carbon precursor, adding ultrasonic treatment conditions in the loaded salt solution environment optimizes the adsorption process, and the intensity of the specific ultrasonic treatment conditions is crucial to the treatment effect in this step, but the optimal parameter point can be found through relevant experimental design.

[0070] In one embodiment, in step S1, the concentration of the caustic solution is 2.0 to 3.0 mol / L, and the immersion time is 8 to 15 hours.

[0071] In this embodiment, when the concentration of KOH solution is reduced, the impregnation time will be extended; when the concentration of KOH is increased, the cost will increase, and the KOH content adsorbed by the sawdust will increase, which may easily lead to excessive pore formation in the subsequent activation stage. In particular, through the combination of concentration and time, the two processes of delignification and alkali activation can be combined, which improves the process efficiency while reducing the cost of the entire process.

[0072] In one embodiment, in step S3, the sulfur and nitrogen source is thiourea, the transition metal source is ferric nitrate, the concentration of thiourea in the loaded salt solution is 0.1 to 0.4 mmol / L, and the concentration of ferric nitrate is 20 to 80 mmol / L.

[0073] In this example, suitable types of sulfur and nitrogen sources and transition metal sources, as well as preferred concentration ranges are given. In subsequent specific examples, it is shown that the loading salt solution in the above concentration range can achieve a better loading effect.

[0074] In one embodiment, in steps S2 and S5, the drying temperature is 50 to 70 degrees Celsius, and the drying time is 4 to 8 hours.

[0075] In this embodiment, preferred parameters of the drying process are provided so as not to form an overly drastic volatilization effect. Execution of the above process can achieve a better drying effect.

[0076] In one embodiment, the temperature of the heating carbonization in step S2 is 680 to 720 degrees Celsius, the heating rate is 4 to 6 degrees Celsius per minute, and the heat preservation is 1.5 to 2.5 hours.

[0077] In this embodiment, the maximum temperature, heating process and holding time of heating carbonization are given, which can form a better carbonization effect.

[0078] In one embodiment, the pyrolysis temperature in step S5 is 880 to 920 degrees Celsius, the heating rate is 4 to 6 degrees Celsius per minute, and the heat preservation is 1.5 to 2.5 hours.

[0079] In this embodiment, the maximum temperature, heating process and holding time of pyrolysis are given, which can form a better pyrolysis effect.

[0080] The present invention also provides an application of a wood-derived three-dimensional porous carbon-based catalyst, wherein the wood-derived three-dimensional porous carbon-based catalyst is used as an oxygen reduction electrocatalyst of a zinc-air battery.

[0081] Through the above-mentioned various parameter tests and comparative analysis with other catalysts, it can be seen that wood-derived three-dimensional porous carbon-based catalysts used as oxygen reduction electrocatalysts in zinc-air batteries have certain advantages in terms of cost and performance.

[0082] Example 1

[0083] The balsa wood block (15 mm * 15 mm * 5 mm) was cut into thin slices with a thickness of less than 1.5 mm along the growth direction to prepare the fiber biomass raw material. A KOH solution with a concentration of 2.5 mol / L was prepared, and the fiber biomass raw material was immersed in the solution for 12 hours to remove a large amount of lignin to obtain a biomass pretreatment product. Then, the obtained biomass pretreatment product was rinsed with deionized water and placed in an oven for drying. Finally, under a protective atmosphere (Ar), the biomass pretreatment product was heated to 700 degrees Celsius at a heating rate of 5 degrees Celsius per minute and kept warm for 2 hours to obtain a three-dimensional porous carbon precursor. 0.404 g of thiourea and 76.2 mg of Fe(NO3)3·9H2O were dissolved in 100 ml of deionized water to prepare an aqueous solution. The three-dimensional porous carbon precursor was placed in the solution, fully immersed for 12 hours, taken out and dried to obtain a three-dimensional porous carbon impregnation sample. Finally, under a protective atmosphere (Ar), the precursor was heated to 900 °C at a heating rate of 5 °C per minute and kept at this temperature for 2 h to obtain a three-dimensional porous carbon-based catalyst (Fe@NSC catalyst). Figure 8 The middle is a scanning electron microscope image of a three-dimensional porous carbon-based catalyst. The three-dimensional porous carbon-based catalyst exhibits a unique three-dimensional porous structure, and the particles on its surface are smaller, which helps to increase the contact area between the material and the electrolyte and air.

[0084] Reference Fig. 9, are the test results of the capacitance-voltage characteristic curve (CV) of Fe@NSC catalyst in 0.1 mol / L KOH electrolyte (N2 saturated and O2 saturated respectively). Compared with the CV graph in N2 saturated electrolyte, the CV curve of Fe@NSC catalyst shows a clear cathode peak in O2 saturated electrolyte, and Fe@NSC catalyst shows the most positive oxygen reduction peak (0.74V), which is close to 0.85V of commercial Pt / C (20%), indicating that Fe@NSC catalyst has ORR electrocatalytic activity.

[0085] Reference Fig.10 , the Fe@NSC catalyst was used as the cathode and a zinc-air battery was assembled, and the specific capacity test was carried out with a zinc-air battery assembled with a commercial 20% Pt / C catalyst. At a current density of 10 mAh per square centimeter, the zinc-air battery with the Fe@NSC catalyst also has a specific capacity of 735 mAh per gram, which is much higher than the battery with the commercial Pt / C catalyst (669 mAh per gram). At the same time, at a current density of 10 mAh per square centimeter, the discharge voltage of the material is also much higher than the discharge voltage of the commercial Pt / C zinc-air battery, which once again proves the great advantage of the material in full battery discharge.

[0086] Comparative Example 1

[0087] Cut balsa wood blocks (15 mm * 15 mm * 5 mm) into slices less than 1.5 mm thick along the growth direction to prepare a homemade fiber biomass raw material. 0.404 g of thiourea and 76.2 mg of Fe(NO3)3·9H2O were dissolved in 100 ml of deionized water to prepare an aqueous solution. The fiber biomass raw material was placed in the solution, fully immersed for 12 hours, taken out and dried to obtain a precursor. Finally, under a protective atmosphere (Ar), the precursor was heated to 900 degrees Celsius at a heating rate of 5 degrees Celsius per minute and kept warm for 2 hours to obtain a CN catalyst (the difference from Example 1 is that there is no delignification and alkali activation process).

[0088] Comparative Example 2

[0089] The balsa wood block (15 mm * 15 mm * 5 mm) was cut into thin slices less than 1.5 mm in thickness along the growth direction to make a homemade fiber biomass raw material. A KOH solution with a concentration of 2.5 mol / L was prepared, and the fiber biomass raw material was immersed in the solution for 12 hours to remove a large amount of lignin. Then, the obtained fiber biomass raw material was rinsed with deionized water and placed in an oven for drying. Finally, under a protective atmosphere (Ar), the fiber biomass raw material was heated to 700 degrees Celsius at a heating rate of 5 degrees Celsius per minute, and kept warm for 2 hours to obtain porous carbon. 0.404 grams of thiourea was dissolved in 100 ml of deionized water to prepare an aqueous solution. The porous carbon was placed in the solution, fully immersed for 12 hours, taken out and dried, and a precursor was obtained. Finally, under a protective atmosphere (Ar), the precursor was heated to 900 degrees Celsius at a heating rate of 5 degrees Celsius per minute, and kept warm for 2 hours to obtain an NSC catalyst (the difference from Example 1 is that the Fe element is not loaded).

[0090] Comparative Example 3

[0091] The balsa wood block (15 mm * 15 mm * 5 mm) was cut into thin slices with a thickness of less than 1.5 mm along the growth direction to prepare a homemade fiber biomass raw material. A 2.5 mol / L KOH solution was prepared, and the fiber biomass raw material was immersed in the solution for 12 hours to remove a large amount of lignin. Then, the obtained fiber biomass raw material was rinsed with deionized water and placed in an oven for drying. Finally, under a protective atmosphere (Ar), the fiber biomass raw material was heated to 700 degrees Celsius at a heating rate of 5 degrees Celsius per minute, and kept warm for 2 hours to obtain porous carbon. Finally, under a protective atmosphere (Ar), the precursor was heated to 900 degrees Celsius at a heating rate of 5 degrees Celsius per minute, and kept warm for 2 hours to obtain an AC catalyst (the difference from Example 1 is that Fe element, N element and S element are not loaded).

[0092] Comparative analysis:

[0093] Example 1, Fe@NSC catalyst;

[0094] Comparative Example 1, CN catalyst, which differs from Example 1 in that no delignification and alkali activation process was performed;

[0095] Comparative Example 2: NSC catalyst, which differs from Example 1 in that no Fe element is loaded;

[0096] Comparative Example 3: AC catalyst, which is different from Example 1 in that no Fe element, N element and S element are loaded.

[0097] Reference Fig.11, N2 adsorption-desorption curve tests were performed on Example 1 and Comparative Examples 1 to 3, all of which showed the comprehensive characteristics of the IV type isotherm. The adsorption amount of the IV type isotherm increased rapidly in the low pressure zone, and an H4 type hysteresis loop appeared, confirming the presence of a large number of micropores and mesopores. The porous structure enables the AC catalyst, CN catalyst, NSC catalyst and Fe@NSC catalyst to have a large specific surface area, which are 1277.3 square meters per gram, 447 square meters per gram, 534.4 square meters per gram and 1183.1 square meters per gram, respectively. The Fe@NSC catalyst presents a three-dimensional porous structure dominated by micropores and mesopores. The presence of micropores can provide more active sites for the catalytic reaction, while the presence of mesopores can produce more defects and transfer channels, thereby promoting the rapid transfer of intermediate products in the reaction process. Therefore, the electrocatalytic material has a reasonable microporous and mesoporous structure, which can effectively promote the ORR reaction process.

[0098] Reference Fig.12 , LSV curve tests were performed on Example 1, Comparative Examples 1 to 3, and commercial Pt / C catalysts. The limiting current density of the Fe@NSC catalyst is closer to that of the commercial Pt / C catalyst. Fig.12 , multiple ORR performance parameters were calculated and the following table was drawn.

[0099]

[0100] The starting potential of the Fe@NSC catalyst is 0.84V, which is closer to the 0.97V of the commercial Pt / C catalyst. At the same time, among the samples, the starting potential of the Fe@NSC catalyst ranks at the top. In the comparison of the half-wave potential of the samples, the half-wave potential of the Fe@NSC catalyst is still a certain distance away from the commercial Pt / C catalyst. However, the Fe@NSC catalyst has the largest half-wave potential in the homemade samples, indicating that it has a higher ORR electrocatalytic activity in the same batch of samples.

[0101] In summary, the wood-derived three-dimensional porous carbon-based catalyst, preparation method and application provided by the present invention introduce Fe, N and S elements into the carbon skeleton, and finally obtain a three-dimensional porous carbon-based catalyst with high specific surface area and loaded with three active elements. The prepared three-dimensional porous carbon-based catalyst has a three-dimensional porous structure, which gives the material an extremely high specific surface area, meaning that the material can fully expose active sites. Benefiting from the unique large specific surface area and highly exposed active sites, the material exhibits excellent oxygen reduction performance. When the three-dimensional porous carbon-based catalyst is used as the cathode of a zinc-air battery, it can provide excellent power density and specific capacity.

[0102] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A wood-derived three-dimensional porous carbon-based catalyst, characterized in that: include: The cellulosic biomass raw material after delignification, activation and pyrolysis is loaded with catalysts containing Fe, N and S elements.

2. A preparation method, applied to the wood-derived three-dimensional porous carbon-based catalyst as claimed in claim 1, characterized in that: include: S1. Immersing the fiber biomass raw material in a caustic solution to perform delignification and alkali activation pretreatment to obtain a biomass pre-treated product, wherein the fiber biomass raw material is processed along the growth length direction, and the caustic solution includes one of a sodium hydroxide solution and a potassium hydroxide solution; S2, washing and drying the biomass pretreatment product with deionized water, and then heating and carbonizing it in an inert atmosphere to obtain an alkali-activated three-dimensional porous carbon precursor; S3, preparing a loaded salt solution by using a sulfur and nitrogen source and a transition metal source; S4, adding the three-dimensional porous carbon precursor into the loaded salt solution to complete impregnation and adsorption, thereby obtaining a three-dimensional porous carbon impregnation sample; S5. Dry the three-dimensional porous carbon impregnation sample, and then pyrolyze it in an inert atmosphere to finally obtain a three-dimensional porous carbon-based catalyst.

3. The preparation method according to claim 2, characterized in that: In the step S1, the fiber biomass raw material is balsa wood chips.

4. The preparation method according to claim 2, characterized in that: In the step S1, ultrasonic treatment conditions are added to the immersion environment of the caustic solution; and in the step S4, ultrasonic treatment conditions are added to the loaded salt solution environment.

5. The preparation method according to claim 2, characterized in that: In the step S1, the concentration of the caustic solution is 2.0 to 3.0 mol / L, and the immersion time is 8 to 15 hours.

6. The preparation method according to claim 2, characterized in that: In step S3, the sulfur and nitrogen source is thiourea, the transition metal source is ferric nitrate, the concentration of thiourea in the loaded salt solution is 0.1 to 0.4 mmol per liter, and the concentration of ferric nitrate is 20 to 80 mmol per liter.

7. The preparation method according to claim 2, characterized in that: In the steps S2 and S5, the drying temperature is 50 to 70 degrees Celsius, and the drying time is 4 to 8 hours.

8. The preparation method according to claim 2, characterized in that: In the step S2, the temperature of the heating carbonization is 680 to 720 degrees Celsius, the heating rate is 4 to 6 degrees Celsius per minute, and the heat preservation is 1.5 to 2.5 hours.

9. The preparation method according to claim 2, characterized in that: In the step S5, the pyrolysis temperature is 880 to 920 degrees Celsius, the heating rate is 4 to 6 degrees Celsius per minute, and the heat preservation is 1.5 to 2.5 hours.

10. An application of the wood-derived three-dimensional porous carbon-based catalyst according to claim 1, characterized in that: The wood-derived three-dimensional porous carbon-based catalyst is used as an oxygen reduction electrocatalyst in zinc-air batteries.